OC-047 A prospective, back-to-back, comparative study of manual spiral enteroscopy and double-balloon enteroscopy. (28th May 2012) - Despott, E J; Murino, A; Bourikas, L A; Nakamura, M; Ramachandra, V; Fraser, C
Abstract : Introduction: By facilitating examination and therapy of the deep small bowel (SB) without recourse to surgery, double-balloon enteroscopy (DBE) has revolutionised SB endoscopy and is now considered to have become the "gold-standard" device assisted enteroscopy (DAE) technology. The more recently developed manual spiral enteroscopy (SE) shows promise to facilitate faster DAE, although whether these two technologies enable similar SB insertion depths remains uncertain. Methods: We performed a prospective, back-to-back comparative study of SE and DBE performed during the same session (under general anaesthesia) in 15 patients (10 women, 5 men; mean age ±SD, 51.4±15.4 years). The aim was to compare SB insertion depths by SE and DBE procedures performed in tandem, in the same cohort, using the same method of SB insertion depth estimation. Comparisons of duration, procedure difficulty (PD) (endoscopists' VAS score) and diagnostic yield (DY) were also performed. SE procedures were performed first and a tattoo was placed to mark the most distal point of SB insertion. Results: In 14 cases, the tattoo placed at SE was reached and passed by DBE; median (95% CI) insertion depths for DBE vs SE were 265 (227 to 324) vs 175 (132 to 212) cm respectively, p=0.004. In one patient, the tattoo placed during SE could not be reached by DBE at an estimated final SB insertion depth of 160 cm. Conversely, the median time taken to achieve deepest insertion was significantly shorter for SE as compared with DBE (median (95% CI) times for SE vs DBE: 24 (20 to 28) min vs 45 (35 to 53) min respectively, p=0.0005). Median procedure duration was also shorter for SE (median (95% CI) duration: SE vs DBE was 28 (27 to 36) min vs 54 (45 to 62) min respectively, p=0.0002. In the 14 patients where comparison was possible, median time taken by SE to reach maximal insertion was not significantly different to the time taken by DBE to reach the tattoo placed at SE (median (95% CI) times for SE vs DBE were 24 (20 to 28) min vs 19 (14 to 26) min respectively, p=0.28). Mean VAS PD scores were similar (mean VAS±SD (95% CI) PD score: SE vs DBE, 5.3±2.3 (4.0 to 6.6) vs 5.2±2.4 (3.9 to 6.5) respectively, p=0.86). Overall DY was similar for both (DY: SE vs DBE, 46.7% vs 53.3% respectively, p=0.4). However, in one case, deeper SB insertion at DBE (median SB insertion at DBE vs SE, 270 cm vs 150 cm respectively) led to the identification of the suspect SB lesion (SB lipoma) which had not been reached by SE. Mild SE-related mucosal trauma was observed in 60% of cases; no other complications were observed in the study. Conclusion: Our experience suggests that although SE may enable faster DAE procedure times, DBE allows for significantly deeper SB insertion. Competing interests: E Despott grant/research support from: Fujifilm & Imotech Medical (UK), A Murino grant/research support from: Fujifilm & Imotech Medical (UK), L Bourikas: None declared, M Nakamura: None declared, V Ramachandra: None declared, C Fraser: None declared.